Impact of Selected Factors On Poultry Death During Transportat And Implications In The Form of Financial Losses - Krzysztof TERESZKIEWICZ; Piotr ANTOS; Wojciech RYBCZYK; Lukasz KULIG (Communications of International Proceedings, 2021)
Animal welfare during processing of poultry is one of the most important aspects contributing to quality of the acquired meat. During transportation of animals to slaughterhouses animals are subjected to various environmental factors such as temperature extrema during summer and winter months. The travel distance between breeding place and slaughterhouse is other important factor  responsible for poultry mortality during transport. To ensure provision of optimal transportation conditions it is important to understand which factors have statistically significant impact on the welfare of poultry identified based on dead on arrival indicator. In this research five variables e.g., transportation month, quarter of the year, temperature, travel distance and  transportation vehicle were investigated whether they have impact on dead on arrival indicator. Moreover financial implications of poultry deaths on arrival were estimated.
Keywords: Animal Transport; Poultry Deaths; DOA Indicator